2010
DOI: 10.1111/j.1574-695x.2010.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine development inStaphylococcus aureus: taking the biofilm phenotype into consideration

Abstract: Vaccine development against pathogenic bacteria is an imperative initiative as bacteria are gaining resistance to current antimicrobial therapies and few novel antibiotics are being developed. Candidate antigens for vaccine development can be identified by a multitude of high-throughput technologies that were accelerated by access to complete genomes. While considerable success has been achieved in vaccine development against bacterial pathogens, many species with multiple virulence factors and modes of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 159 publications
(159 reference statements)
0
79
0
2
Order By: Relevance
“…In the phenotypic biofilm production, the MDR isolates produced biofilms strongly; exhibiting that biofilm production can highly affect the extent of antibiotic resistance among multidrug-resistant isolates. The majority of healthcare associated MRSA harbor the SCCmec type III, according to previous results (17)(18)(19). Also these MRSA were significantly more resistant to antibiotics, enhancing the idea that these isolates have caused hospital acquired infections (20,21).…”
Section: Discussionmentioning
confidence: 67%
“…In the phenotypic biofilm production, the MDR isolates produced biofilms strongly; exhibiting that biofilm production can highly affect the extent of antibiotic resistance among multidrug-resistant isolates. The majority of healthcare associated MRSA harbor the SCCmec type III, according to previous results (17)(18)(19). Also these MRSA were significantly more resistant to antibiotics, enhancing the idea that these isolates have caused hospital acquired infections (20,21).…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, since biofilms are involved in 80% of human bacterial infections (Harro et al 2010), it is crucial to extend the studies on biofilm inhibition and AMP dispersion effects to already preformed biofilms and to developing biofilms. Also, synergism studies involving AMPs are needed to discover successful AMP-AMP or AMP-drug combinations for lowering the dosage and minimizing the side effects of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of human bacterial infections are caused by biofilms (Harro et al 2010), mainly health care associated infections related to the implant of medical devices, eg urinary catheters, intravascular catheters and prosthetic heart valves. As such, microbial adhesion onto surfaces and the subsequent formation of biofilms are critical concerns for many biomedical applications (Donlan and Costerton 2002;Fey 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The possible target sites for vaccine development may be the bacterial cells within the biofilm and/or biofilm matrix (Harro et al, 2010). Cerca et al, (2007) reported that an antibody developed against Staphylococcus Poly-N-acetyl glucosamine (PNAG) was found effective against different strains of E. coli.…”
Section: Biofilm As the Vaccine Targetmentioning
confidence: 99%
“…Sepsis and pneumonia are mainly caused by planktonic forms whereas, a whole range of diseases, namely, endophthalmitis, osteomyelitis, endocarditis, chronic skin infections, indwelling medical device infections, chronic rhino-sinusitis, and dental implantits are caused by the biofilmic form of the bacteria. Abscess can be caused by both of the forms (Harro et al, 2010). Staphylococci are human pathogen, known for their ability to become resistant to antibiotics.…”
Section: Introductionmentioning
confidence: 99%